Association of size-resolved number concentrations of particulate matter with cardiovascular and respiratory hospital admissions and mortality in Prague, Czech Republic - Braniš, Martin; Vyškovská, Jana; Malý, Marek; Hovorka, Jan (Inhalation toxicology, 2010)
We analyzed the association of particle number and PM(2.5) concentrations with mortality and cardiorespiratory hospital admissions in Prague. Number concentrations of submicron particles in the range of 15-487 nm were measured continuously at a central site in 2006. The particle number concentrations were integrated into four groups with count median diameters of 31 (NC(31)), 128 (NC(128)), and 346 nm (NC(346)). The total number concentration of submicron particles 15-487 nm (NC(tot)) was also constructed. The studied health outcomes were the daily hospital admissions due to cardiovascular and respiratory diseases and daily cardiovascular and respiratory mortality and the total mortality. The Poisson regression was used for data analysis. The strongest association was found for the accumulation mode particles (NC(346)) (RR 1.164, 95% CI: 1.052-1.287 for cardiovascular and 1.334, 95% CI: 1.126-1.579 for respiratory admissions for a 7-day moving average for 1000 particles per 1 cm(3) increase). Reasonable association between both the cardiovascular and respiratory admissions and NC(346) was also found for lag 0, lag 1, lag 2 (not for respiratory admissions), and the 4-day moving average. For NC(128) and NC(tot), the association was also significant for both cardiovascular and respiratory admissions at lag 0, lag 1, and lag 2 (not for respiratory admissions) for the 4-day and 7-day moving average. The association between the PM(2.5) and daily cardiovascular hospital admissions was significant at 2-day lag and for a 4-day average. Positive association with respiratory admissions was significant only for a 7-day average. No association was found between the studied air pollution variables and daily mortality.
Keywords: pevné částice; Hospitals; Urban Health; poruchy dýchání; velikost částic; nemocnice; Particle Size; znečištění ovzduší; lidé; Air Pollution; Particulate Matter; Air Pollutants; Cardiovascular Diseases; zdraví ve městech; Czech Republic; kardiovaskulární nemoci; vystavení vlivu životního prostředí; Česká republika; Respiration Disorders; látky znečišťující vzduch; Environmental Exposure; Humans